Membangun Basis Data Posyandu Menuju Indonesia Sehat Sentosa - Indrajani Indrajani (Bina Nusantara University, 2013)
The purpose of this research is to analyze and design a database to support Pos Pelayanan Terpadu (POSYANDU). Search data techniques implemented include interviews, documentation, observation, and literature study. Analysis and database design include conceptual, logical, and physical design. The result of this research is a database system that can save integrated data and POSYANDU information needs. Using the database system, PUSKESMAS can manage data of mother and baby’s health and related transactions.